2006
DOI: 10.1136/emj.2005.029231
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an extended scope physiotherapy service on patient satisfaction and the outcome of soft tissue injuries in an adult emergency department

Abstract: Objectives: To evaluate the effect of introducing an extended scope physiotherapy (ESP) service on patient satisfaction, and to measure the functional outcome of patients with soft tissue injuries attending an adult emergency department (ED), comparing management by ESPs, emergency nurse practitioners (ENPs), and all grades of ED doctor. Methods: The ESP service operated on four days out of every seven in a week in an urban adult ED. A satisfaction questionnaire was sent to all patients with a peripheral soft … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
134
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(137 citation statements)
references
References 13 publications
3
134
0
Order By: Relevance
“…(25)(26)(27) Only one of these studies compared treatment provided by an ESP and other professionals and this study was the first to describe an ESP service in an emergency department. (26) It was shown that 55% of patients were independently managed by the ESP and a follow-up suggested higher patient satisfaction with the ESP service.…”
Section: Discussionmentioning
confidence: 99%
“…(25)(26)(27) Only one of these studies compared treatment provided by an ESP and other professionals and this study was the first to describe an ESP service in an emergency department. (26) It was shown that 55% of patients were independently managed by the ESP and a follow-up suggested higher patient satisfaction with the ESP service.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported higher satisfaction ratings when patients in the ED were seen by a physiotherapist. 56 The veterans' healthcare system in Salt Lake City reported that their program reduced the Investigations describing the relationship between patient recovery and this approach to care are notably lacking. One study using a randomized design, however, did analyze patient outcomes associated with ED-based physical therapy.…”
mentioning
confidence: 99%
“…Patient satisfaction with their management by EDPs has been reported as higher than those managed in the traditional model for musculoskeletal injuries 8,12 and for mechanical lower back pain. 11 Interestingly, however, one study noted a significantly greater time period for return to usual activity for patients with soft tissue injuries managed by EDPs, 12 so it can be seen that the clinical effectiveness of physiotherapy in ED requires attention and deliberation in some contexts.…”
Section: Introductionmentioning
confidence: 99%
“…8 Ensuring that patients managed by physiotherapists fall within the scope of practice of the profession is a significant responsibility for physiotherapists working in a primary contact capacity, in both the context of emergency or in a private community clinic. Awareness of which cases can be safely managed by a physiotherapist is important for EDPs, and to ensure patient safety from a service delivery perspective, clear guidelines should exist for appropriate selection of patients by EDPs, as well as the transferral of care to an ED medical officer should a patient's requirements extend beyond the scope of the physiotherapy profession.…”
Section: Challenges To Considermentioning
confidence: 99%